Influência da água residuária da suinocultura sobre a acidez do óleo do pinhão manso (Jatropha curcas L.) - Bastos, Rafaela Koglin (2016)
The increased interest in biofuels in recent years, coupled with the problem of the need for environmental sanitation in different areas of the economy justify the proposal of this work, which is the reuse of wastewater from swine (SW) in the jatropha crop (Jatropha curcas L.) and its influence on oil acidity - short parameter importance in the production of biodiesel; culture stands out from oilseeds for its oil production capacity and high adaptability in different scenarios. The experiment featured a Jatropha plantation area of 900 m², which were used 216 m² for conducting the experiment, divided into eighteen installments, the research was conducted over three years; each year the plots received six treatments with different proportions of SW with three repetitions each, applications were performed in triplicate with an interval of three months between each application. Seed harvest was done by hand during the entire production plan period from the first application of each year, the oil was extracted with solvent (ethanol), justified because it is cheaper, less toxic and less harmful to the environment, when compared to other organic solvents such as hexane. The acidity was determined by titration process with sodium hydroxide (NaOH) at the end of each experimental cycle; further the composition was determined as the percentage of oils of fatty acids (FA) by gas chromatography. The results showed an inversely proportional reduction of acidity amount of SW applied during the three years analyzed; It was also observed a decrease in linolenic acid concentration due to the increase of the applied dose and in all cycles. Knowing FA unsaturated oils leave them more susceptible to oxidation, reduction FA that may be related to decreased acidity